Biosleeving with epiphytic bacteria as a novel approach to oviposition deterrence against the cocoa pod borer conopomorpha cramerella (Snellen) (Lepidoptera: Gracillariidae) - Ibrahim Yusof, Sha'ari Shari Fuddin, (Universiti Pendidikan Sultan Idris, 2016)
Biosleeving with epiphytic bacteria as a novel approach to oviposition deterrence against the cocoa pod borer conopomorpha cramerella (Snellen) (Lepidoptera: Gracillariidae) by Ibrahim Yusof, Sha'ari Shari Fuddin,